Native American Y-STR haplotyping: its forensic relevance in Argentina - Sala, Adriana Andrea (2013)
Y-STR markers, namely YHRD minimal haplotype with additional DYS437, DYS438, and DYS439 markers, were investigated in a set of 236 samples of individuals belonging to Mataco–Guaycurú speaking tribes, inhabiting communities in Northern and Central Argentina. One specific Amerindian Y-SNP was also typed in order to identify Native Y chromosomal haplotypes. Our results show that 86% of the samples belong to haplogroup Q-M3 and 67% of the haplotypes were unique and never found before in the YHRD database.